Effect of the Experiential Learning Program on Rational Drug Use Competency in Pediatric Patients Among Nursing Students - Vongchulachat, Sudarat; Insing, Sunee (Journal of health and health management, 2026)
This one-group pretest-posttest quasi-experimental research aimed to compare mean rational drug use knowledge scores before and after program participation; evaluate clinical and OSCE performance skills after the program; and assess students’ satisfaction with the program. The samples consisted of 61 third-year nursing students from Saint Louis College, selected using a stratified random sampling method. The research instruments consisted of 1) The experiential learning program (CVI = 1.00); 2) the knowledge questionnaire (KR-20 = 0.73); 3) the clinical skills evaluation form (reliability = 0.74); 4) the OSCE skills assessment form (CVI = 0.97); and 5) the program satisfaction survey (reliability = 0.90). Data were analyzed using percentage, mean, standard deviation and Paired t-test. The results are as followings; 1) The students’ mean knowledge score after the experiment ( = 41.16, SD = 4.78) was significantly higher than the mean score before the experiment ( = 34.2, SD = 4.43), p < .001; 2) the mean clinical performance skills was at a very good level ( = 3.85, SD = .09); 3) the mean OSCE-based skills was at a good level ( = 2.65, SD = .15); 4) satisfaction with the program was at the highest level ( = 4.74, SD = .33). The research findings demonstrate that the program effectively enhances students’ pediatric rational drug use competency. Consequently, it is recommended that experiential learning should be implemented in other clinical nursing practicum courses.